The impact of SARS-CoV-2 on healthcare workers of a large University Hospital in the Veneto Region: risk of infection and clinical presentation in relation to different pandemic phases and some relevant determinants - Liviero, Filippo; Volpin, Anna; Furlan, Patrizia; Battistella, Monica; Broggio, Alessia; Fabris, Laura; Favretto, Francesco; Mason, Paola; Cocchio, Silvia; Cozzolino, Claudia; Baldo, Vincenzo; Moretto, Angelo; et al. (Frontiers in Public Health, 2023)
Aim: To evaluate the incidence of SARS-CoV-2 infection and the prevalence of COVID-19-related symptoms in relation to pandemic phases and some relevant variables, in a cohort of 8,029 HCWs from one of the largest Italian University Hospital. Methods: A single-center retrospective study was performed on data collected during SARS-CoV-2 infection surveillance of HCWs. Cox's multiple regression was performed to estimate hazard ratios of SARS-CoV-2 infection. Logistic multivariate regression was used to assess the risk of asymptomatic infections and the onset of the most frequent symptoms. All analyses adjusted for socio-demographic and occupational factors, pandemic phases, vaccination status and previous infections. Results: 3.760 HCWs resulted positive (2.0 - 18.6% across five study phases). The total incidence rate of SARS-CoV-2 infection was 7.31 cases per 10,000 person-days, significantly lower in phase 1 and higher in phases 4 and 5, compared to phase 3. Younger HCWs, healthcare personnel and unvaccinated subjects showed a higher risk of infection. Overall, 24.5% were asymptomatic infections, with a higher probability for male, physician, HCWs tested for screening, fully vaccinated, and for those with a previous infection. The clinical presentation changed over the phases in relation to vaccination status and the emergence of new variants. Conclusion: The screening activities of HCWs allowed for the early detection of asymptomatic cases limiting the epidemic clusters inside the hospital wards. SARS-CoV-2 vaccination reduced infections and symptomatic cases, demonstrating again its paramount value as a preventive tool for occupational and public health.